Knowledge, Attitudes, and Practice of Pelvic Floor Muscle Training in People With Spinal Cord Injury: A Cross-Sectional Survey - Sato-Klemm, Maya; Williams, Alison M. M.; Mortenson, W. Ben; Lam, Tania (Frontiers in Rehabilitation Sciences, 2022)
Background: There is emerging evidence that pelvic floor muscle training (PFMT) may be useful for treating some urogenital conditions in people with spinal cord injury (SCI). Future clinical investigations would benefit from understanding the extent to which people with SCI are aware of and practicing PFMT, and their attitude towards this therapy. Objective: The goal of this study was to assess the knowledge, attitudes, and practices related to PFMT among people with SCI. Methods: We distributed an internet survey internationally via SCI related organizations for two months. We used descriptive statistics to summarize each survey item, and Chi-square and Mann-Whitney U tests to explore the differences in results between sexes and level of motor-function. Results: Complete data from 153 respondents were analyzed. Sixty-two percent of respondents were female and 71% reported having complete paralysis. More than half of respondents reported being aware of PFMT (63%); more females than males reported knowledge of PFMT (p = 0.010). Females (p = 0.052) and people with partial paralysis (p = 0.008) reported a stronger belief that they would benefit from PFMT. Few people with SCI had practiced PFMT (20%), and of those who practiced, most of them had SCI resulting in partial paralysis (p = 0.023). Conclusions: While people with SCI may be aware of and have favorable attitudes towards PFMT, few had practiced PFMT and there were notable differences in attitudes towards PFMT depending on the sex and level of motor function of the respondents.